Phytochemical Constituents of the Bark of Vitex negundo L. - Dhakal, Ram Chandra; Rajbhandari, Meena; Kalauni, Surya K.; Awale, Suresh; Gewali, Mohan. B. (Journal of Nepal Chemical Society, 2009)
p-Hydroxybenzoic acid (1) and β-sitosterol (2) were isolated, and identified from the methanol and hexane extracts of Vitex negundo. The structure of the compounds were established on the basis of spectral analysis. Keywords: p-hydroxybenzoic acid, β-sitosterol, vitex negundo. DOI: 10.3126/jncs.v23i0.2101 Journal of Nepal Chemical Society, Vol. 23, 2008/2009 Page: 89-92